Новые сведения о систематике немертин семейства Cratenemertidae (Enopla, Monostilifera) - Чернышев, А.В. (Вестник зоологии, 1993)
Cratenemertes varia-bilis and Amphiporus arenarius are transferred to the genus liipponnemeries. Collarene-meries gen. n. is established for Amphiporus bimaculalus, distinct by bifurea 1 channels of the cerebral organs and skin collar forming at head drawing in. The family Cratenemer-tidae is insigned to Monostylifera. The class Enopla is divided into 3 orders: Monostyli-fera B r i n k m a n n, 1917, stat. n., Polystylifera Brink m a n n , 1917, stat. n., and Bdellonemertini V e r r i l l, 1892.